Pengawasan Dewan Perwakilan Rakyat Papua Terhadap Keputusan Gubernur Provinsi Papua Tentang Upah Minimum Propinsi 2018 - Bayu Satria Muis Ali Patong; Aminuddin Ilmar; Muhammad Yunus Wahid (Nagari Law Review, 2020)
This research is normative legal research. The approach used in this study uses a statutory approach and a conceptual approach. This research was carried out in the Province of Papua by taking locations in the offices of the People's Representative Council (DPR) of the Province of Papua and the Government Office of the Province of Papua. The results showed that the response of aspirations or complaints from the public was conveyed to members of the Papua Parliament in many forms. Both aspirations are conveyed verbally (dialogue) the delivery of aspirations in public by voicing their demands and the aspirations delivered in written form (official). Aspirations in writing should be addressed to the Chairperson of the Papuan Parliament through the Council Secretary in writing. Supervision that has been carried out by the Papua Province Parliament for the 2014-2019 period is the absorption of aspirations that does not represent all workers /laborers in Papua Province. There are members of the Papua Parliament who are less able to make optimal use of the work meeting supervision activities. The average of the attendance of Papuan DPR members at parliament hearings only 40 at the most of the 69 Papuan DPR members present. Likewise, working visit activities that rarely all members of the commission are present at work visits or there must be some who are absent. The lack of active members of the Papua Parliament in the form of supervision that has been carried out will certainly affect the supervisory performance of the Papua Parliament. The steps of the Provincial Government of Papua to hold discussions with worker/labor representatives to find the best solution is the best way is to revise the amount of the 2018 Provincial Minimum Wage (UMP) to Rp. 3,000,000. However, this value still doesn’t meet the formulation, that is 9.93% of 8.71% decided by decree of Labor Minister